Technical efficiency in water and sanitation providers in Chile - Ferro, Gustavo (2015)
Chile has achieved universal levels of coverage in water, sewerage and sewerage treatment in urban areas. Also, the providers exhibit complete cost recovering, universal metering and diminishing consumption. On the other hand, the regulatory model in use is criticized because it does not solve the asymmetric information among regulator and providers. Based on a sample of 18 providers, we computed an input distance function through stochastic frontier analysis. We explore comparative technical efficiency in the sector, concentrating our attention in the recent years, looking for responses to new challenges related with loss reduction, maintenance expenditures, and lower tariffs.